2012
DOI: 10.1002/jemt.22077
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic progenitor constituents and adherent cell progenitor morphology isolated from black‐rumped agouti (Dasyprocta prymnolopha, Wagler 1831) bone marrow

Abstract: Stem cells are present in the adult tissues of most diverse species. Bone marrow is recognized to be the most exploited site to obtain stem cells and cell progenitors. The objective of the present study was to characterize hematopoietic progenitor (HP) morphology and analyze the performance of adherent cell progenitors (ACPs) cultivated in vitro from black-rumped agouti bone marrow (Dasyprocta prymnolopha). Bone marrow aspirates were obtained from tibia crest and used to prepare histological slides and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Innumerous discrepancies have been observed, such as the positive identification of the STRO-1 marker in stromal MSC [31,32] and absence of this marker in the adipogenic MSC [33,34]. The conflict persists among studies with MSC isolated from the same anatomic niche and has been identified as CD 10 positive by [32] and negative by [35] and [36]. The most suitable identification method for MSC is prolonged proliferation in culture with morphology maintenance and differentiation capacity in at least two cell lines [28,31,30].…”
Section: Discussionmentioning
confidence: 99%
“…Innumerous discrepancies have been observed, such as the positive identification of the STRO-1 marker in stromal MSC [31,32] and absence of this marker in the adipogenic MSC [33,34]. The conflict persists among studies with MSC isolated from the same anatomic niche and has been identified as CD 10 positive by [32] and negative by [35] and [36]. The most suitable identification method for MSC is prolonged proliferation in culture with morphology maintenance and differentiation capacity in at least two cell lines [28,31,30].…”
Section: Discussionmentioning
confidence: 99%
“…Half of the dose of the same combination was used to maintain the anesthesia. 7 The blood pressure, heart, and respiratory rate were monitored throughout the procedure.…”
Section: Anesthesia Protocolmentioning
confidence: 99%
“…The agouti is a rodent that has been extensively studied , Menezes et al 2003, Azevêdo et al 2008) and which shows biological and physiological characteristics favorable for use in experimental research as a animal model (Fortes et al 2005, Conde-Júnior et al 2012, Rocha et al 2012. Bone marrow mononuclear cells of this animal were injected to treat induced renal injury (Cabral et al 2012) and in culture undifferentiated cells were obtained through the isolation and expansion by several passages (Rocha et al 2012).…”
Section: Introductionmentioning
confidence: 99%